2012
DOI: 10.4172/2167-0943.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity in Whey Proteins Influencing Energy Balance

Abstract: Obesity develops due to energy (food) intake exceeding energy expenditure. Nutrients that reduce the positive energy balance are thus being considered as therapies to combat obesity. Here, we review the literature related to the physiological, cellular and endocrine effects of intake of whey proteins, namely α-lactalbumin, β-lactoglobulin, glycomacropeptide and lactoferrin. Moreover, we discuss how dietary composition and obesity may influence whey protein effects on the above parameters. Evidence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In the obese state, the effects of WPI on energy intake appear to be lost, yet dietary proteins still attenuate HFD-induced obesity ( 10 , 20 23 ) . The discrepancies between these data and those of the present study, in particular, with regard to energy intake, may be related to the differences in dietary macronutrient and micronutrient composition (45 % energy as fat v. 60 % energy as fat, casein v. soya as the control and altered Ca content in the diet) and/or the study duration (8 weeks v. up to 20 weeks) that were used to assess the energy balance impact of whey proteins ( 19 ) . It is also possible that some of these discrepancies may have arisen due to the fact that we subjected the group-housed mice to a single housing environment of the TSE Phenomaster cages (TSE systems) to measure their energy intake.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the obese state, the effects of WPI on energy intake appear to be lost, yet dietary proteins still attenuate HFD-induced obesity ( 10 , 20 23 ) . The discrepancies between these data and those of the present study, in particular, with regard to energy intake, may be related to the differences in dietary macronutrient and micronutrient composition (45 % energy as fat v. 60 % energy as fat, casein v. soya as the control and altered Ca content in the diet) and/or the study duration (8 weeks v. up to 20 weeks) that were used to assess the energy balance impact of whey proteins ( 19 ) . It is also possible that some of these discrepancies may have arisen due to the fact that we subjected the group-housed mice to a single housing environment of the TSE Phenomaster cages (TSE systems) to measure their energy intake.…”
Section: Discussionmentioning
confidence: 66%
“…Also, using healthy lean subjects or rodents, a number of studies have reported a short-term reduction in energy intake and an increase in thermogenesis following WPI intake in comparison with other dietary proteins including casein ( 7 , 11 – 13 ) . Although there are discrepancies ( 14 17 ) , it is largely recognised that WPI intake influences the balance between energy intake and energy expenditure in the lean state ( 18 , 19 ) . In contrast, the effects of WPI on energy intake and energy expenditure in the HFD-induced state are less well known, although WPI has consistently been shown to reduce HFD-induced body-weight gain and adiposity ( 10 , 20 23 ) .…”
mentioning
confidence: 99%
“…Because of the specific amino acid composition including branched chain amino acids, intake of these proteins has been shown to bring about several health benefits. Notably, a diet supplemented with whey protein has been found to modulate appetite, and ileal expression and plasma levels of satiety hormones such as insulin, ghrelin, cholecystokinin, and glucagon-like peptide 1 (Chungchunlam, Henare, Ganesh, & Moughan, 2015;McAllan, D Cotter, & M Roche, 2012;Pal, Radavelli-Bagatini, Hagger, & Ellis, 2014). Additionally, in several studies in which whey protein constituted the main protein source of a high-fat diet (HFD), this protein ameliorated the impairment of glucose tolerance, and reduced the increase in body weight and adiposity compared to other dietary proteins, such as casein (CAS, a nonwhey milk protein which is the main component of cheese), soy, meat, and fish proteins (Madsen, Myrmel, Fjaere, Liaset, & Kristiansen, 2017;McAllan et al, 2013;Pilvi, Korpela, Huttunen, Vapaatalo, & Mervaala, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that eating WP causes the decrease in calorie intake, increased basal energy expenditure, and modulates insulin sensitivity and glucose homeostasis, leading to changes in lipid metabolism in adipose tissue, liver, and muscle [ 39 42 ]. The AMPK and adiponectin are key molecules to metabolic responses in different tissues [ 43 , 44 ]; they are involved in the preventive response against negative physiological processes caused by the consumption of a diet high in saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is plenty of evidence suggesting that the intake of WP may lower consumption of calories, increase baseline energy expenditure, and improve insulin sensitivity and glucose homeostasis, thus leading to changes in lipid metabolism in adipose tissue, liver, and muscle [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%